Fathers’ experience and perceptions of parent alienation in high-conflict divorce - Bosch-Brits, Elsabé; Wessels, Cornelia; Roux, Adrie (Social Work/Maatskaplike Werk, 2018)
This research focuses on providing social workers with a deeper insight into fathers’ experience and perceptions of parent alienation in instances of high-conflict divorce. An exploratory and interpretative research design was used in this qualitative study. Data were collected by means of in-depth interviews with each participant individually as well as by field notes made by the researcher. It was clear from the research that fathers experience parent alienation as traumatic or negative at several levels of functioning. Parent alienation is a reality and the necessity for further research on this phenomenon was clearly evident.